The Uji Teori Institusional: Pengungkapan Emisi Karbon, Leverage, Profitabilitas, dan Nilai Perusahaan - Budiman, Lucky Satria; Yadiati, Winwin; Abdul Hasyir, Dede (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study examines the impact of carbon emission disclosure, leverage, and profitability on firm value using institusional theory Research methodology: The research uses quantitative data from 10 energy companies listed on IDX (Indonesia Stock Exchange) between 2018-2022. The sample technique used was purposive sampling. Panel data regression is employed to analyze the data. Carbon emission disclosure is measured by GRI-305 (Global Reporting Initiative – 305), leverage by DAR (Debt-to-Asset) and profitability by EPS (Earning per Share) as independent variable, then firm value by PBV (Price Book Value) as dependent variable. Results: Carbon emission disclosure has a positive but insignficiant effect on firm value, leverage has a significant negative effect, while profitability shows a negative but insignificant effect on firm value. Limitations: The study’s sample size was limited due to the removal of outliers to meet classical assumption test, which may reduce the sample’s representativeness but improves data analysis quality. Contribution: This research is useful for investors, academics, companies, government, and the general public who want to know the benefits of carbon emissions disclosure, and the level of readiness of the Indonesian capital market in addressing climate change issues and disclosure of carbon emissions by companies.